The International and Political Journal: Financial crises and the dilemma of strategy building in American foreign policy in the era of George W. Bush and Barack Obama: a comparative study - Mahmoud, Lecturer Dr.Khaled Rashid (The International and Political Journal, 2024)
Financial crises have not been subject to study and scrutiny except as a process or condition that the economy is going through, as a cycle of instability, or as an indicator of the economy’s unhealthy condition. As for it being a decisive factor in making and implementing the foreign policies of the countries that fall under its influence at all levels, it has not been the focus of attention of researchers in foreign policy affairs. This study attempts to shed light on the impact of financial crises on building foreign policy strategies. The global financial crisis of 2007-2008 provided us with an ideal model for applying the study’s hypothesis, which indicates the close relationship between financial crises and the policies that countries follow in implementing their strategies (United States of America in the eras of George W. Bush and Barack Obama: a model). Studying the impact of the global financial crisis on the American strategy is important, because it explains to us how the influence process takes place, how the American decision-maker faced the crisis and how it was reflected in the tools and means he used in implementing his strategy. Based on the above, the study discussed the impact that the global financial crisis had on the American economy and the change that occurred in this strategy between the era of former President George W. Bush from 2001-2009, and President Barack Obama from 2009-2013, and reached the most prominent results: that financial crises force the decision maker Based on the least expensive means for implementing various types of internal and foreign policies, and this is what appeared in the context of American behavior before and after the crisis.